Fatal Rhinocerebral mucormycosis in a patient with ulcerative colitis receiving azathioprine and corticosteroid - Narges Najafi; Firoozeh Kermani; Nahid Gholinejad Ghadi; Seyed Reza Aghili; Zahra Seifi; Emmanuel Roilides; Tahereh shokohi (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Rhinocerebral mucormycosis is a rare fatal fungal infection which is on a growing trend, particularly among immunocompromised patients. Immunosuppressive drugs, including corticosteroids and antimetabolites, increase the risk of this infection. Herein, we reported the case of fulminant rhinocerebral mucormycosis in a patient with ulcerative colitis receiving azathioprine and corticosteroid. Case report: A 58-year-old woman was admitted to the hospital in a state of coma with an extensive necrosis in her nose. She was afflicted with intestinal bleeding after 1 month of fasting and was treated with azathioprine and a high dose of prednisolone for ulcerative colitis 2 months prior to hospital admission. The direct microscopic examination of the necrotic tissues of the paranasal sinuses showed several non-septate hyphae consistent with Mucorales. Culture media yielded Rhizopus species, which was identified as Rhizopus oryzae by internal transcribed spacer polymerase chain reaction sequencing. Despite the implementation of surgical and pharmaceutical (liposomal amphotericin B) treatments, the patient expired after 2 weeks of admission. Conclusion: The gastroenterologists should be aware of the adverse effect of immunosuppressive drugs they prescribe for the treatment of inflammatory bowel disease.